DEHYDRATION OF CHEESE BY HOT AIR, MICROWAVE AND FREEZE-DRYING - ANA RITA C. PINHO; FERNANDA R. ASSIS; ANA PAULA PERES; MANUELA E. PINTADO; ALCINA M. M. B. MORAIS (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The objective of this work was to study the dehydration of skim cheese through different methods, in particular by hot air, microwave and freeze-drying, in order to assess which of these methods would be more suitable for the development of a new product (cheese snack). For the three processes of dehydration, several temperatures, powers and times were used, respectively. The drying time was optimized to allow the water activity of the final product to be between 0.3 and 0.4. The color and texture of the product obtained by the three processes were evaluated, and the nutritional analysis (protein, lipids, ash) of the product dried by hot air at 52 ºC and by microwave at 750 W and 850 W was performed. The sensory analysis of the microwave dehydrated products was also carried out. The results obtained revealed that the temperature played a relevant role in the drying time and the hardness of the product. In the dehydration by microwave, the power of 850 W resulted in a lower drying time and a better color preservation, but in a high hardness of the samples. Among the three processes studied, the microwave drying was the fastest for the water removal from the cheese.